Inspiratory muscle training combined with pursed lip technique in women with chronic obstructive pulmonary disease: a case study - Anna Arnal-Gómez; Irene Davia-Ruiz; Gemma Victoria Espí-López (Karolinum Press, 2020)
Objective. To improve pulmonary function, exercise capacity and quality of life of two women with Chronic Obstructive Pulmonary Disease (COPD). Material and Methods. Study of two clinical cases, both women. An intervention of 8 weeks was performed, in which the patients performed 3 weekly sessions, of which 1 was performed with supervision of the physiotherapist and 2 sessions were performed at home. The treatment sessions consisted of inspiratory muscle training with an inspiratory threshold and controlled breathing exercises with the pursed lip technique. Results. Quality of life of both women improved at the end of the study. In the woman with severe COPD, Maximal Inspiratory Pressure (MIP) and Maximal Expiratory Pressure (MEP) increased after the intervention. The Peak Expiratory Flow (PEF) improved in both cases, but not the rest of the spirometric values. Dyspnea improved in the woman with moderate COPD but not in the case of the one with severe COPD. Finally, the distance walked in the 6MWT improved in both cases. Conclusions. The training of the inspiratory muscles together with the pursed lip technique positively influences quality of life and exercise capacity of two women with COPD.